2017
DOI: 10.7860/jcdr/2017/24747.9827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lung Lesions at Autopsy: A Histopathological Study

Abstract: Introduction: Autopsies are carried out to establish the identity, cause of death, time of death, and ante-mortem or post-mortem nature of death. These help in establishing the cause of death and ascertain the disease process which led to death. Aim:To study the prevalence and pattern of lung diseases in medicolegal autopsies, confirmed by histopathological examination. Materials and Methods:This retrospective study was carried out in the Department of Pathology. Tissue bits from lungs, retrieved at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 5 publications
4
22
0
Order By: Relevance
“…2,3,5,6 Emphysematous changes were seen in 15(4.31%) cases in present study which is consistent with Chauhan G et al, Amin NS et al and Khare P et al 7.76%, 6.6% and 8.75% cases respectively. 3,6,11 Among the extra pulmonary cause of death in which lung showed associated findings were most commonly of edema, congestion, CVC in 53.16% cases in our study. This is comparable to study done by Udayashankar SK et al Chauhan G et al and Bal MS et al which showed 54.54%, 54.32% and 58% cases respectively.…”
Section: Discussionmentioning
confidence: 79%
“…2,3,5,6 Emphysematous changes were seen in 15(4.31%) cases in present study which is consistent with Chauhan G et al, Amin NS et al and Khare P et al 7.76%, 6.6% and 8.75% cases respectively. 3,6,11 Among the extra pulmonary cause of death in which lung showed associated findings were most commonly of edema, congestion, CVC in 53.16% cases in our study. This is comparable to study done by Udayashankar SK et al Chauhan G et al and Bal MS et al which showed 54.54%, 54.32% and 58% cases respectively.…”
Section: Discussionmentioning
confidence: 79%
“…[ 11 ] Pratima et al . [ 12 ] and Chandani et al . [ 13 ] cases of emphysema were 6.5%, 8.9% and 4.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In a smaller study from India, including 86 cases, the prevalence of lung pathology findings in autopsies was 65%. This is higher compared to our study, but the authors included congestion and edema caused by cardiac failure in their list of diagnoses [ 20 ]. Apart from that, the range of pathologies comprised mainly inflammatory diseases.…”
Section: Discussionmentioning
confidence: 63%